Dissecting Outcomes: Should Cytoreductive Nephrectomy Be Performed for Patients With Metastatic Renal Cell Carcinoma With Sarcomatoid Dedifferentiation? - Adashek, Jacob J.; Zhang, Yumeng; Skelton, William Paul; Bilotta, Alyssa; Chahoud, Jad; Zemp, Logan; Li, Jiannong; Dhillon, Jasreman; Manley, Brandon; Spiess, Philippe E. (Frontiers in Oncology, 2021)
Background: It is highly contested whether cytoreductive nephrectomy for treating advanced renal cell carcinoma (RCC) with sarcomatoid features (sRCC) benefits overall survival. Patients with sRCC are known to have a poor prognosis, and these tumors have a more aggressive biology than those without sarcomatoid features. Methods: Patients with clear cell RCC or non–clear cell RCC underwent cytoreductive nephrectomy in efforts to improve overall survival (OS). Patients were stratified by presence or absence of histologic sarcomatoid features within tumor samples. Results: Of 167 patients who underwent cytoreductive nephrectomy, 127 had clear cell RCC, of whom 14 had sarcomatoid features, and 40 had non–clear cell RCC, of whom 13 had sarcomatoid features. Median age of the cohort was 62 years (range, 56.5-69 years). The cohort included 119 male (71.3%) and 48 (28.7%) female patients. Among all patients with advanced RCC, having sRCC had a significantly worse OS after cytoreductive nephrectomy (30 vs 8 months; hazard ratio [HR], 2.88; P <0.0001). Additionally, favorable-risk patients had significantly longer OS compared to intermediate- or poor-risk patients (56 vs 30 vs 10 months; HR, 0.21; P =0.00016). For patients with clear cell RCC, having sRCC conferred a significantly poorer survival (30 vs 9 months; HR, 2.82; P =0.0035). Patients with non–clear cell sRCC also had significantly worse outcomes compared to patients whose tumors did not have sarcomatoid features (30 vs 6.5 months; HR, 3; P =0.009). When patients with sRCC were stratified by whether there was >10% or ≤10% sarcomatoid features present within the sample, there was no significant difference in OS (8 vs 8.5 months; P =0.32). Conclusions: Sarcomatoid features within tumor histology confer significantly poor prognosis. Patients with sRCC, regardless of clear cell vs non–clear cell histology, have significantly shorter OS. Even among patients with 10% or less sarcomatoid features, there was no OS benefit to cytoreductive nephrectomy. Based on our findings, there appears to be a limited to no role of cytoreductive nephrectomy if sRCC is identified on pretreatment biopsy. The role of radiomics and pre-operative biopsies may confer significant benefit in this patient population.